Revision of the subgenus Scymnus (Parapullus) Yang from China(Coleoptera: Coccinellidae) - Chen, Xiao-Sheng; Ren, Shun-Xiang; Wang, Xing-Min (Zootaxa, 2012)
The subgenus Scymnus (Parapullus) Yang, 1978 is herein revised. Eight species of the Parapullus fauna are known tooccur in China up to the present. The following five species are described as new to science: Scymnus (Parapullus) adun-catus sp. nov., S. (P.) malleatus sp. nov., S. (P.) nanlingicus sp. nov., S. (P.) parallelicus sp. nov., S. (P.) solus sp. nov..Diagnoses, colorized illustrations and distributions are provided for each species. A key to the Chinese species is also presented.